The Effect of Price, Product Quality and Promotion on Consumer Buying Interest in the Originote Skincare - Yhosi Fatmalah Sari; Evi Fitrotun Najiah; Mohammad Yaskun (Sean Institute, 2024)
The purpose of the research is to know the effects of the disease, the quality of the process and the process of the process of the development of the process of the development of the Skinlcare Thle Origlinote. Quantitative research methods, methods of conducting interviews, questionnaires and observations. The Slkincare Tlhe Originote clone is the clone of Slkincare Tlhe Originote. A sample of 96 responses was used. The results of the research show that the quality of the product and the product have a positive effect on the quality of the product, and the quality of the product and the quality of the product, which means that it is both partial and simultaneous to the interest in buying the Skincare Tlhe Orliginote Skincare Package. Vlariabel promlosi make up lvarliabel ylang palling domlinan affects consumer buying interest in The Originote Skincare.